Correlation between VCAM-1 Level and Absolute Monocyte Count in Coronary Artery Disease - Anastasha Faustine; Andreas Arie Setiawan; Dwi Retnoningrum; Ariosta Ariosta (Indonesian Association of Clinical Pathologist and Medical laboratory, 2024)
To prove the correlation between VCAM-1 level and absolute monocyte count among Coronary Artery Disease (CAD) patients. The study was an observational analytic study with a cross-sectional approach. The research subjects were 74 CAD patients who had been proven by coronary angiography and were treated in the Cardiology Department of Central General Hospital by Dr. Kariadi Semarang. This study was conducted from March to July 2021. VCAM-1 levels were examined with the ELISA method, using BioTek ELX800 Microplate reader (USA), and absolute monocyte count was analyzed with flow cytometry method, using Hematology Analyzer SYSMEX XN-1000 (Japan). Statistical analysis was done by Pearson's correlation coefficient test, in which p<0.05 was considered significant. The mean VCAM-1 level was (361.78±128.01) ng/mL. The mean absolute monocyte count was (0.48±0.17) ×103/µL. The result of the Pearson correlation test showed a moderate positive correlation between VCAM-1 levels and absolute monocyte count in CAD patients (p=0.00; r=0.46). There was a moderate positive correlation between VCAM-1 level and absolute monocyte count in CAD patients. A positive correlation exists between VCAM-1 level and absolute monocyte count among CAD patients.